2017
DOI: 10.7324/japs.2017.70930
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and antiparasitic activities of clovamide: the major constituent of Dichrostachys cinerea (L.) Wight et Arn

Abstract: The application of different chromatographic and spectroscopic techniques to the aqueous alcoholic leaves extract of Dichrostachys cinerea (L.) Wight et Arn. (Mimosaceae) led to the isolation and identification of ten phenolic compounds. Among them, apigenin-7-O-apiosyl (1→2) glucoside, chrysoeriol-7-O-apiosyl (1→2) glucoside and clovamide were isolated for the first time from the plant. The rest of the compounds are: flavonol glycosides (quercetin-3-O-rhamnopyranoside, quercetin-3-O-glucopyranoside, myricetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…As mentioned previously, clovamide has been reported as a potent inhibitor of influenza A subtype H5N1 (virus) and T. evansi (protozoa;El-Sharawy et al, 2017). Niehues et al (2011) determined that clovamide can partially inhibit adherence of Heliobacter pylori to gastric epithelial cells, an important factor in H. pylori virulence.…”
Section: Antimicrobial Activity/enzyme Inhibition Of Clovamide and Pomentioning
confidence: 80%
See 2 more Smart Citations
“…As mentioned previously, clovamide has been reported as a potent inhibitor of influenza A subtype H5N1 (virus) and T. evansi (protozoa;El-Sharawy et al, 2017). Niehues et al (2011) determined that clovamide can partially inhibit adherence of Heliobacter pylori to gastric epithelial cells, an important factor in H. pylori virulence.…”
Section: Antimicrobial Activity/enzyme Inhibition Of Clovamide and Pomentioning
confidence: 80%
“…(Yoshihara et al, 1977;Kolodziejczyk-Czepas et al, 2017), Vernonia fastigiata (Masike et al, 2017), Dalbergia spp. (Van Heerden et al, 1980;El-Sharawy et al, 2017), Acmella oleracea (Nascimento et al, 2020), and cacao (Sanbongi et al, 1998). Clovamide has garnered considerable attention for its potential human health benefits as an anti-inflammatory and neuroprotective compound (Park et al, 2007(Park et al, , 2017Fallarini et al, 2009;Zeng et al, 2011;Kolodziejczyk-Czepas et al, 2017;Tsunoda et al, 2018) and as an anti-microbial with activity against the human pathogens influenza A subtype H5N1 (El-Sharawy et al, 2017), Trypanosoma evansi (same source), and Heliobacter pylori (Niehues et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] have revealed that the plant is used to treat elephantiasis. Indeed, El-Sharawy et al [9] showed the anti-parasitic effect of phytochemical constituents of Dichrostachys cinerea.…”
Section: Traditional Uses Against Ntdsmentioning
confidence: 99%
“…Dichrostachys cinerea, also known as sicklebush, Bell mimosa, Chinese lantern tree, or Kalahari Christmas tree, is a fast growing tree of up to 7 m height, traditionally used as laxative, diuretic and to treat dysentery, elephantiasis, gonorrhoea, boils, headache, syphilis, sore, worms [6, 7], inflammation, and cancer [8]. Previous phytochemical analysis of Dichrostachys cinerea led to the identification of a triterpenoid β -amyrin glucoside, apigenin-7- O -apiosyl (1→2) glucoside, chrysoeriol-7- O -apiosyl (1→2) glucoside, clovamide, quercetin-3- O -rhamnopyranoside, quercetin-3- O -glucopyranoside, myricetin-3- O -rhamnopyranoside, myricetin-3- O -glucopyranoside, myricetin, apigenin, and kaempferol from the leaves [6, 9] as well as the meroterpene derivatives, dichrostachines A-R from the bark and roots [10]. Preliminary cytotoxicity investigations of this plant were reported towards DU145 and 22Rv1 prostate cancer cells and HeLa cervical cancer cells [7].…”
Section: Introductionmentioning
confidence: 99%